Contextualizing Parent–School Partnerships: A Comparative Study of Community-Based Collaboration Models in Two Jakarta Kindergartens - Mardiyah, Dede; Sutanto, Bedjo; Fuad, Nurhattati (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates community-based models of parent–school collaboration within early childhood education (ECE) in urban Jakarta, focusing on two contrasting institutions: TKIT Nurul Iman (East Jakarta) and TK Avicenna (South Jakarta). Using a qualitative case study approach, which includes participant observation, in-depth interviews, and document analysis, the research explores the dynamics, modalities, and contextual factors that facilitate or hinder collaborative practices. Findings reveal that TKIT Nurul Iman exemplifies a symbolic–religious model of collaboration, shaped by emotional, spiritual, and communal ties. In contrast, TK Avicenna represents an administrative–transactional model, characterised by formalised procedures and structured institutional involvement. The study proposes a typology of parent–school collaboration grounded in sociocultural and institutional dimensions, highlighting how localised practices are shaped by urban spatiality, religious orientation, and organisational culture. These insights provide practical implications for designing inclusive and context-sensitive family engagement policies in Early Childhood Education (ECE), particularly in diverse urban settings such as Jakarta. By centring sociocultural factors, this research contributes to the broader discourse on participatory education and localised educational governance.